Synchronous online discussion: teaching English in higher education amidst the covid-19 pandemic - Rinekso, Aji Budi; Muslim , Ahmad Bukhori (Universitas Muhammadiyah Sidoarjo, 2020)
During the outbreak of Covid-19 pandemic, many educational institutions have adapted various online teaching modes. However, studies exploring the employment of synchronous online discussion for teaching English in higher education context were still limited. This study aimed at investigating EFL university students’ perceptions and challenges on the use of synchronous online discussions. Employing virtual observations and semi-structured interviews, five Master students of English education study program of a public university in Bandung participated in this study. Data were based on three domains of communication types for e-learning; content-related, planning of tasks and social supports. The findings showed that the students had positive response to the employment of synchronous online discussion. They believed that synchronous online discussion was a good online teaching mode where task negotiation, task planning, opinions, questions and answers can be done easily. In addition, they could improve critical thinking and writing skills as well as get social supports. Meanwhile, poor internet connection and misunderstanding of tasks became the challenge. HIGHLIGHTS Covid-19 pandemic demands the employment of online learning mode. Synchronous online discussion offers distinctive features for accommodating higher education learning, specifically in the teaching of English. Data analysis based on three domains namely content-related, planning of tasks and social supports would be administered.